Association between the alpha-actinin-3 and angiotensin-converting enzyme gene polymorphisms and middle power in elite male collegiate judo athletes - Agemizu, K.; Itaka, T.; Hirokawa, S.; Aruga, S.; Machida, S. (Research Journal of Budo, 2016)
Previous studies have reported that the alpha-actinin-3 (ACTN3) and angiotensin-converting enzyme (ACE) gene polymorphisms are associated with sports performance, muscle strength, muscle power, and endurance. Competitive judo requires high levels of muscle power, muscle strength, and endurance. However, thus far, associations between these gene polymorphisms and muscle power in judo athletes have not been reported. The purpose of this study was to investigate the relationship between ACTN3 and/or ACE gene polymorphisms and middle power in judo athletes. This study recruited 79 male judo athletes from a top-level university in Japan. Genomic DNA was extracted from the saliva sample taken from each athlete. Genotyping using either polymerase chain reaction (PCR)-restriction fragment length polymorphism or PCR was performed to detect ACTN3 (rs1815739) and ACE (rs1799752) gene polymorphisms. Each athlete also performed a 30-s Wingate anaerobic test with a resistance equal to 4.5% of the athlete`s body weight.